Sedentary time and markers of inflammation in people with newly diagnosed type 2 diabetes - Falconer, C.L.; Cooper, A.R.; Walhin, J.P.; Thompson, D.; Page, A.S.; Peters, T.J.; Montgomery, A.A.; Sharp, D.J.; Dayan, C.M.; Andrews, R.C. (Elsevier, 2014)
Background and aims: We investigated whether objectively measured sedentary time was associated with markers of inflammation in adults with newly diagnosed type 2 diabetes.